2007
DOI: 10.1021/jf0701032
|View full text |Cite
|
Sign up to set email alerts
|

Plant P5C Reductase as a New Target for Aminomethylenebisphosphonates

Abstract: A series of N-substituted derivatives of aminomethylenebisphosphonic acid were evaluated as potential inhibitors of delta1-pyrroline-5-carboxylate reductase (EC 1.5.1.2), the enzyme that catalyzes the last step in proline biosynthesis, partially purified from Arabidopsis thaliana suspension cultured cells. At millimolar concentrations, three compounds out of 26 were found to interfere with the catalytic mechanism. One of them, namely, 3,5-dichloropyridyl-aminomethylenebisphosphonic acid, retained such inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 36 publications
(39 reference statements)
3
51
0
Order By: Relevance
“…This inhibitory activity was observed when studying bleaching herbicides influencing biosynthesis of caretonoids. Further studies have shown that herbicidal aminomethylene-bisphosphonates may be considered multi-target substances, which was documented by their inhibitory activities towards glutamine synthetase, [198,199] 3-deoxy-D-arabinoheptulosonate-7-phosphate (DAHP) synthase, [200] δ 1 -pyrroline-5-carboxylate (P5CR) reductase [201,202] and pyrophosphatase [203]. Thus, these compounds may be considered a heterogeneous group of compounds with variable modes of action (Scheme 11).…”
Section: Plant Growth Regulatorsmentioning
confidence: 99%
“…This inhibitory activity was observed when studying bleaching herbicides influencing biosynthesis of caretonoids. Further studies have shown that herbicidal aminomethylene-bisphosphonates may be considered multi-target substances, which was documented by their inhibitory activities towards glutamine synthetase, [198,199] 3-deoxy-D-arabinoheptulosonate-7-phosphate (DAHP) synthase, [200] δ 1 -pyrroline-5-carboxylate (P5CR) reductase [201,202] and pyrophosphatase [203]. Thus, these compounds may be considered a heterogeneous group of compounds with variable modes of action (Scheme 11).…”
Section: Plant Growth Regulatorsmentioning
confidence: 99%
“…Since this dual anabolic route is shared also by plants (Lehmann et al 2010), P5C reductase inhibitors might find application in crop protection as well. We previously synthesized and screened several derivatives of aminomethylenebisphosphonic acid (compound 01) for the ability to inhibit plant P5C reductase (Forlani et al 2007). A group of phenyl derivatives were found effective in the micromolar to millimolar range, and indeed showed phytotoxic properties (Forlani et al 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…Some phosphonate inhibitors were indeed found to exert both phytotoxic (Forlani et al 2007(Forlani et al , 2008 and antibiotic (Forlani et al 2011) effects. Here we report the results of a thorough biochemical characterization of P5CR from S. pyogenes, shedding more light on its substrate preference and reaction mechanism.…”
Section: Introductionmentioning
confidence: 99%